2013
DOI: 10.1371/journal.pone.0080423
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pulse-Chase SILAC Strategy Measures Changes in Protein Decay and Synthesis Rates Induced by Perturbation of Proteostasis with an Hsp90 Inhibitor

Abstract: Standard proteomics methods allow the relative quantitation of levels of thousands of proteins in two or more samples. While such methods are invaluable for defining the variations in protein concentrations which follow the perturbation of a biological system, they do not offer information on the mechanisms underlying such changes. Expanding on previous work [1], we developed a pulse-chase (pc) variant of SILAC (stable isotope labeling by amino acids in cell culture). pcSILAC can quantitate in one experiment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…As an essential molecular chaperone that assures the correct folding and maturation of a number of cellular proteins, Hsp90 inhibition leads to a global repression of protein synthesis and an increase in the degradation of its client proteins. 58 This finding is consistent with our observation that KU-596 also decreased a subset of 25 ribosomal proteins only in diabetic Hsp70 KO sensory neurons. A recent proteomics study using human T cells revealed that Hsp90 inhibition resulted in the depletion of proteins involved in transcription and DNA damage response as well as a mild but general decrease of ribosomal proteins and other components of the protein synthesis machinery.…”
Section: Resultssupporting
confidence: 92%
“…As an essential molecular chaperone that assures the correct folding and maturation of a number of cellular proteins, Hsp90 inhibition leads to a global repression of protein synthesis and an increase in the degradation of its client proteins. 58 This finding is consistent with our observation that KU-596 also decreased a subset of 25 ribosomal proteins only in diabetic Hsp70 KO sensory neurons. A recent proteomics study using human T cells revealed that Hsp90 inhibition resulted in the depletion of proteins involved in transcription and DNA damage response as well as a mild but general decrease of ribosomal proteins and other components of the protein synthesis machinery.…”
Section: Resultssupporting
confidence: 92%
“…[74], in order to study how HSP90 inhibition with GA affects the proteome in T cells [75]. Seventeen percent of all proteins were impacted by GA, with upregulation of proteins involved in protein folding and stress response, including HSP90 and co-chaperones AHSA1, CDC37, STIP1, and FKBP4, but intriguingly not AARSD or FKBP5, suggesting that GA may remodel the HSP90 chaperone complexes.…”
Section: Global Impact Of Hsp90 Inhibition On the Proteomementioning
confidence: 99%
“…Protein turnover is not only important to maintain protein concentrations in the cell, but also to allow for changes. Modulation of the proteome is necessary for most cellular responses, involving modifications in general or specific protein turnover (3,4). Neurons also have the ability to modulate and adjust their proteome in response to specific cues, for example, synaptic remodeling in response to patterns of action potentials in neurons.…”
mentioning
confidence: 99%